Characterization of cerebral malaria in the outbred Swiss Webster mouse infected by Plasmodium berghei ANKA - Martins, Yuri Chaves (2009)
Acknowledgments To Marilene Damazio dos Santos and Luiz Carlos da Silva from the Leônidas Deane Animal House for caring mice. To Belmira Santos from the Fiocruz Animal House for providing the Swiss Webster and the CBA mice. To Rodrigo Mexes from the Service of Image Treatment and Production for treating the images.